2009
DOI: 10.1088/0004-637x/695/2/1376
|View full text |Cite
|
Sign up to set email alerts
|

Outflow-Driven Turbulence in Molecular Clouds

Abstract: In this paper we explore the relationship between protostellar outflows and turbulence in molecular clouds. Using 3-D numerical simulations we focus on the hydrodynamics of multiple outflows interacting within a parsec scale volume. We explore the extent to which transient outflows injecting directed energy and momentum into a sub-volume of a molecular cloud can be converted into random turbulent motions. We show that turbulence can readily be sustained by these interactions and show that it is possible to bro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 27 publications
5
99
1
Order By: Relevance
“…This is demonstrated by recent simulations of outflow-driven turbulence which reveal that energy injection by outflows is not capable of creating turbulence at scales comparable to the cloud size. Models of interacting outflows generated either randomly (Carroll et al 2008), or self-consistently (Nakamura & Li 2007) show that turbulence is only injected with an effective driving scale of about 1/5 to 1/10 the size of the cloud (λ D /L c ≈ 0.1-0.2) which is incompatible with our results as summarized in Figs. 1 and 5.…”
Section: Disfavored On Energetic Grounds (Mac Low and Klessen 2004)contrasting
confidence: 91%
“…This is demonstrated by recent simulations of outflow-driven turbulence which reveal that energy injection by outflows is not capable of creating turbulence at scales comparable to the cloud size. Models of interacting outflows generated either randomly (Carroll et al 2008), or self-consistently (Nakamura & Li 2007) show that turbulence is only injected with an effective driving scale of about 1/5 to 1/10 the size of the cloud (λ D /L c ≈ 0.1-0.2) which is incompatible with our results as summarized in Figs. 1 and 5.…”
Section: Disfavored On Energetic Grounds (Mac Low and Klessen 2004)contrasting
confidence: 91%
“…If measured outflow extents range from ∼0.1 to 2 pc then they will not contribute driving motions on larger scales. Magnetohydrodynamic simulations of outflow-driven turbulence confirm that the peak of the velocity power spectrum occurs at the maximum length scale of the driving outflows (Carroll et al 2009(Carroll et al , 2010.…”
Section: Discussionmentioning
confidence: 83%
“…Recent numerical simulations have demonstrated that protostellar outflows can indeed inject turbulent motions into cluster-forming clumps (Li & Nakamura 2006;Nakamura & Li 2007;Carroll et al 2009Carroll et al , 2010Wang et al 2010;Hansen et al 2012). A common drawback of this type of simulations is the use of periodic boundary conditions, which prevent the outflows from leaving the simulation box, leading to an overestimate of the efficiency of outflow feedback.…”
Section: Analytic Model Of Outflow-regulated Cluster Formationmentioning
confidence: 99%